Meneguhkan identitas nasional di tengah arus globalisasi digital - Jannah, Wildanul Wildanul Jannah (Maliki Interdisciplinary Journal, 2026)
In the era of digital globalization, the rapid development of technology provides easy access to the internet and social media, which brings an ambivalent impact on Indonesia’s national identity. On one hand, digitalization presents a golden opportunity for the community to introduce local culture, traditions, and historical uniqueness to the international stage. On the other hand, the unstoppable influx of foreign culture threatens the existence of local cultural values, erodes the traditional values of the younger generation, and triggers a decline in the proper use of regional and national languages. Based on a literature review and synthesis of phenomena, this paper aims to analyze the challenges of digital globalization and formulate strategies to strengthen national identity. The proposed strategies include integrating nationalism-based education, instilling local culture from an early age, and campaigning for the consistent use of the Indonesian language in digital spaces. Furthermore, the younger generation plays a vital role through the phenomenon of ’digital nationalism’, where national values are expressed through creative content, hashtags, and works that blend local culture with modern styles. Through this collaboration, national identity is projected to survive and be globally appreciated.